Using Twitter and the mobile cloud for delivering medical help in emergencies. (25th April 2017) - Alshareef, Hazzaa Naif; Grigoras, Dan
Summary: Emergency events require a fast response and decisions based on first‐hand information. This paper presents a mobile cloud service that makes the best use of social media applications, such as Twitter, in emergency and risk management. Here, risk and emergency teams can receive data that can inform their decisions in a matter of seconds when an emergency has affected areas under their management. The proposed service allows users to provide on‐the‐ground information regarding such an event, as well as early notification to people who are in the vicinity of an emergency situation. The service matches users' requests to a set of predefined labels that will help rescuers to understand the situation more clearly. The service was implemented and tested with Android devices and a cloud‐computing instance hosted on an Amazon platform. A cloud‐based tool is also provided for risk and emergency management teams to interact with users' requests. The experimental results show that the proposed mobile cloud service enhanced the early detection of emergencies. This paper also provides a review of research papers on the use of social media in risk and emergency management and the benefits of integrating social media with mobile cloud computing to provide a better healthcare service in emergencies.